SPECIAL MISSIONS IN MULTILATERAL DIPLOMACY - Bjelica Vlajić, Iris; Stanković, Vladan (ACADEMIC REVIEW, 2025)
Special missions have the longest tradition and are undertaken to fulfill a specific task or objective at the highest level. They are temporary in nature, which is why they differ from permanent diplomatic missions. There are gaps in the universal regulation of some forms of special missions. The goal of the research is to determine and present the rules that regulate the rights and obligations of states when multilateral conferences are organized by the state, because these rules are only partially covered by existing international conventions. For this purpose, methods of content analysis, historical and comparative methods, and methods of induction and deduction were used. The result of the research shows that a large number of rules applicable to special missions when conferences are organized by international organizations can also be applied to conferences organized by states, but there are rules conditioned by the specifics of this type of multilateral diplomacy. After the conducted research, the conclusion is that there is still a need for special missions in multilateral diplomacy and that the rules governing the privileges and obligations of mission members are established by customs, international documents and state legislation.